Biomechanical Analysis Of Countermovement Jump Performance Among Sports Players With Flatfoot And Normal Foot Structures (Applied Biological Research, 2023)
The purpose of this study was to compare the kinetic parameters of counter movement jump between sports players in flatfoot and normal foot groups. In  this cross-sectional study, random sampling method was used to draw a group  of 20 players with normal foot and a group of 20 players with flatfoot. Navicular  drop test was used to classify two groups (flat foot and normal foot). Quattro  Jump Kistler force platform (model 9290DD) was used to record kinetic  parameters of Countermovement jump. The findings of this study showed that  the players with flatfoot exhibited higher peak vertical ground reaction forces  (VGRFs) (p < 0.001) and lower push-off force impulse (p < 0.001) than players  in normal foot group; however, no significant differences were observed in jump  height and average force between the normal foot and flatfoot groups (p > 0.05).  The results revealed that flatfoot has no effect on jump height but have  significant impact on other kinetic parameters of jump performance. Players  with flatfoot produced higher VGRFs during landing which may lead to greater  forces imposed on foot region as compared to the players with normal foot which  can induce various musculoskeletal injuries.
Keywords: Countermovement jump; flatfoot; kinetics; Quattro Jump Kistler force platform